CircCDR1as Suppresses Bone Microvascular Endothelial Cell Activity and Angiogenesis Through Targeting miR‐135b/ FIH‐1 Axis. Issue 2 (22nd February 2021) - Mao, Zheng; Liu, Gang; Xiao, Gui‐Yang; Zhao, Chang; Zou, Yu‐Cong
Abstract : Objective: The current study investigated the role of CircCDR1as on angiogenesis of bone microvascular endothelial cells (BMECs) isolated from non‐traumatic ONFH. Methods: Forty corticosteroid‐induced ONFH patients received THA were enrolled in our study. Expressions of CircCDR1as, miR‐135b, and FIH‐1 were detected by qRT‐PCR in affected necrosis tissue and non‐affected normal tissue. Bone microvascular endothelial cells (BMEC) were isolated from six patients and treated with 0.1 mg/mL hydrocortisone to establish a GC‐damaged model of BMECs. Circ CDR1as plasmid and miR‐135b mimic were transfected into BMECs. BMEC proliferation was assessed using MTT assays. The migration ability of cells was detected by scratch‐wound assays. Matrigel assay was performed to detect angiogenesis in vitro . Western blot assay was used to detect HIF‐1α, VEGF, and FIH‐1 expressions. FISH, RNA pull down, RIP, and luciferase assay were carried out to determine the interaction of CircCDR1as, miR‐135b, and FIH‐1. Results: CircCDR1as was upregulated(2.02 ± 0.30 vs . 1.00 ± 0.10, P  < 0.001) whereas miR‐135b was downregulated (0.55 ± 0.12 vs . 1.00 ± 0.10, P  < 0.001) in affected tissues than in non‐affected tissues. Expression of CircCDR1as and FIH‐1 were negatively associated with miR‐135b in affected tissues (CircCDR1as with miR‐135b: r = −0.506, P < 0.001; FIH‐1 with miR‐135b r = −0.510, P  < 0.001). Total blood tubule density was increased when CircCDR1as was silenced compared with NC ( P  < 0.01 vs . NC). The number of migrated BMECs were significantly increased in CircCDR1as silencing group compared with NC group ( P  < 0.05 vs . NC). In addition, CircCDR1as plasmids transfection increased the protein expressions of FIH‐1 ( P  < 0.05 vs . NC) and reduced the HIF‐1α as well as VEGF expression compared with NC group ( P  < 0.05 vs . NC). FISH, RNA pull down, RIP, and luciferase assay identified that FIH‐1 was a target of miR‐135b and could be modulated by CircCDR1as. Conclusion: CircCDR1as decreases angiogenesis and proliferation of BMECs by sponging miR‐135b and upregulate FIH‐1. Abstract : Total tubule density was increased when CircCDR1as was silenced compared with NC. 2. The number of migrated BMECs were significantly increased in CircCDR1as silencing group compared with NC group, whereas markedly decreased migrated BMECs were observed in the CircCDR1as overexpression group.